Trial Watch: Toll-like receptor agonists in cancer immunotherapy - Smith, Melody; García-Martínez, Elena; Pitter, Michael R; Fucikova, Jitka; Spisek, Radek; Zitvogel, Laurence; Kroemer, Guido; Galluzzi, Lorenzo (Oncoimmunology, 2018)
Toll-like receptor (TLR) agonists demonstrate therapeutic promise as immunological adjuvants for anticancer immunotherapy. To date, three TLR agonists have been approved by US regulatory agencies for use in cancer patients. Additionally, the potential of hitherto experimental TLR ligands to mediate clinically useful immunostimulatory effects has been extensively investigated over the past few years. Here, we summarize recent preclinical and clinical advances in the development of TLR agonists for cancer therapy.